Intraoral lipoma with degenerative changes mimicking atypical lipomatous tumor: an immunohistochemical study - Silva, Evânio Vilela [UNESP]; Silveira, Heitor Albergoni [UNESP]; Panucci, Beatriz Zamboni Martins; Molena, Kelly Fernanda; Almeida, Luciana Yamamoto [UNESP]; Bufalino, Andreia [UNESP]; León, Jorge Esquiche (Universidade de São Paulo. Agência de Bibliotecas e Coleções Digitais, 2023)
Lipomas are mesenchymal neoplasms relatively uncommon in the oral cavity. Lipomas can exhibit histopathological features mimicking atypical lipomatous tumors (ALT) or dysplastic lipoma (DL) in the presence of degenerative changes. Relevantly, immunohistochemistry assists in the correct diagnosis. Herein, we present the case of a 54-year-old male with a sessile nodule located on the dorsum of the tongue. The histopathological analysis showed a diffuse, non-circumscribed adipocytic proliferation constituted by cells of variable size containing cytoplasmic vacuoles and displaced nuclei, some resembling lipoblasts supported by fibrous connective tissue stroma. By immunohistochemistry, tumor cells were positive for vimentin, S100, FASN, CD10, and p16. Rb expression was intact. Moreover, CD34, p53, MDM2, and CDK4 were negative. After 2-year of follow-up, no alteration or recurrence was observed. In conclusion, MDM2, CDK4, p53, and Rb immunomarkers can be used reliably to differentiate benign lipoma with degenerative changes from ALT and DL.
Keywords: Immunohistochemistry; Lipoma; Liposarcoma; Mouth